Distribution Approximations for Cointegration Tests with Stationary Exogenous Regressors. - Boswijk, H; Doornik, J (John Wiley & Sons, Ltd., 2005)
The distribution of a functional of two correlated vector-Brownian motions is approximated by a Gamma distribution. This functional represents the limiting distribution for cointegration tests with stationary exogenous regressors, but also for cointegration tests based on a non-Gaussian likelihood. The approximation is accurate, fast and easy to use in comparison with both tabulated critical values and simulated p-values. The proposed procedure is applied to a UK model investigating purchasing power parity.